From green hype to green habits: Understanding the factors that influence young consumers' green purchasing decisions - Lopes, João M. (2023)
It is believed that environmental causes will grow in fervor with members of Gen Z. This study explores the main factors of green marketing affecting young Portuguese green purchasing decisions and the relationship between them. An online questionnaire was used to collect data from 708 young Portuguese consumers of eco-friendly products. The quantitative analysis was performed using the partial least squares (PLS) method. We found that the marketing factors of green willingness to purchase, green awareness of price, green perceived benefits, and green perceived quality were positively associated with young peoples' environmental concerns, and they also proved to be positively related to their green purchasing decisions when mediated by the environmental concern variable. This study contributes to the literature on green marketing, having empirically evaluated, for the first time, the role of environmental concerns as mediators of consumers' perceptions of green products and their purchase intentions. Furthermore, it pioneeringly explores the determinants of Generation Z's environmental concerns and green purchasing decisions, making an essential contribution to the literature on consumer behavior and generational cohorts. The breadth of influence of each determinant is not balanced, and producers, marketers, and policymakers must consider these results in their strategy of attracting young consumers to purchase green products.